Prototipe Aplikasi Pembelajaran Bagi Anak Berkebutuhan Khusus dengan Menerapkan Pendekatan Gamification - Tri Sagirani; Nunuk Wahyuningtyas; Sri Hariani Eko Wulandari; Wawan W Efendi (Jurnal Teknik, 2020)
Outbreaks of Corona Virus Disease (COVID-19) require the entire community to change, including education. The government issued a home study policy to reduce the spread of the virus. For students, studying at home relatively does not pose significant obstacles. Whereas for disabilities students, they need learning methods which able make them think that they are studying at school because there are scheduled lessons such as at school and material content that interests them in learning. So, they can concentrate on receiving the material. All learning processes must make it easier for parents to assist them in learning. This study provides a solution through learning media for disabilities in the form of an android-based application using a gamification approach that utilizes elements of character, challenges, interactive, stories, feedback and freedom to fail. This application presents convenience for parents in creating a child's daily schedule, selecting activities that are suitable for disabilities students and providing space for parent and child collaboration. For children, this application can help to stay enthusiastic in learning like at school in a more fun way. The limited trial application uses the System Usability Scale (SUS) as a benchmark for the perception of system usability, with a result of 85,3 which means it has a grade B grade with an Adjective Rating Excellent.